European Strategies in Lifelong Learning A Critical Introduction - Lima, Licínio C. (Study guides in Adult Education, 2011)
Lifelong learning and education is a key concept for the development of adult education as an area of practice and theoretical consideration. In recent decades, meanwhile, the idea of lifelong education and learning has been central to the guidance of various international organisations of many countries.